Effect of Automotive Insurance as a Driving Operation for Behavior in Traffic (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This study was to analyze the insurance function as a abolishing motivating operation to the traffic accidents punishment in a simulation called Game of Transit. Two groups with 5 participants each, with permanent CNH and with Permission, respectively, were submitted to the Game developed in VBA/Excel in Excel 2010 software. They chose paths from the upper left corner to the lower right corner of the 5X5 board during 11 conditions, Baseline and conditions in which the participant was not assured and in others was, each with 6 minutes. Having points accounted, generating 0.05 cents each 10,000 points. Possessing or not insurer, did not assume the Abolishing Operations function on the behavior of all participants in committing accidents. Seven participants were under the control of reflexive motivational operations, avoiding the aversive contingencies. This should concern the institutions responsible for handling accidents, since they do not record driving control variables at times of accidents.
Keywords: Transit; Punishment; Motivational Operation; Accident; Safety